Techno-economic assessment of co-pyrolyzed kitchen waste and rice straw for co-generation of heat and power - Nyambura, Samuel Mbugua; Li, Chao; Xu, Jialang; Wang, Jufei; Li, Hu; Zhang, Zhaotong; V. Bertrand, Gbenontin; Ndumia, Joseph Ndiithi; Li, Xiaolin; Atsbha, Musie Welldegerima; Chin, Bridgid (2023)
Increasing concerns relating to depletion of fossil fuels and global warming coupled with significant growth in waste-to-energy markets have propelled the need for ingenious and flexible technologies that can effectively transform waste biomass into fuels and power at high efficiency. In this study, a comprehensive techno-economic investigation was undertaken to investigate the economic potential of utilizing co-pyrolyzed kitchen food waste and rice straw in a waste to heat and power facility based on microwave pyrolysis and a combined heat and power system. The study involved microwave pyrolysis experiments to investigate the effects of blending proportions of kitchen food waste and rice straw on the evolution of synthetic gas components based on gas chromatography analysis. The optimal blending proportion was then used to run the Aspen Plus heat and power plant simulation. Boiler efficiency, steam cycle thermal efficiency, electrical efficiency, and overall system efficiency were 96.30 %, 36.46 %, 41.61 %, and 35.11 %, respectively. The model had an estimated annual power production of 744,576 kWh/year, hot water production capacity of 1,727,649 L/year, and annual biochar production of 162,045 kg/year. A positive net present value was observed for the project after the second year, coupled with an internal rate of return of 0.62 and a profitability index of 3.85 over ten years. The heat generated can meet rapidly increasing urban heating needs and the power will contribute to grid stabilization. Sensitivity analysis revealed that the greatest potential performance improvements can be achieved by increasing biochar selling price and reducing total investment costs and total annual operating costs. Overall, the study shows scaled-up microwave-based heat and power technology to be a profitable and effective waste management and renewable energy solution.